Igniting Students’ Language Study-Skill: An Overview of the Practice of English Literary Material - Abd Halim; Nur Mutmainna Halim (Journal of English Education and Teaching, 2022)
Detail English literary materials were selected and processed to establish a course-book to be implemented in Junior-High Schools. The materials were designed to ignite students’ language study skills namely inspiration, interactivity and creativity as important aspects in English education. The study was a developmental research and experimental study. The data were collected through (a) an English essay test involving different difficulty levels of questions (cognitive, analytic, evaluative and creative), and (b) classroom observation and interview. Results from this study identified that the learning processes and learning results clearly reflected the three language study skills. By providing and facilitating proper interactive reading materials and a lively atmosphere of classroom discussion, students got inspired to get their own ideas, got free to write their own sentences and this circumstance assigned students to become more creative. Such content of an inspirational, interactive and creative course book must be relevant to the students’ preferences like interest and need to induce students think critically by relating things into facts.